The Effect of Canva-Based Video Media in Christian Religious Education Learning on the Learning Outcomes of Grade VIII Students of SMP Negeri 2 Mantangai - Linta; Matius Timan Herdi Ginting; Lukas (CV Edujavare Publishing, 2026)
The Effect of Canva-Based Video Media in Christian Religious Education Learning on the Learning Outcomes of Eighth-Grade Students at SMP Negeri 2 Mantangai. The low learning outcomes of eighth-grade students at SMP Negeri 2 Mantangai in Christian Religious Education (CRE) served as the background of this study. Preliminary data indicated that only 41.18% of students achieved the Minimum Mastery Criterion (MMC) of 75, which was attributed to the dominance of conventional teaching methods. This study aimed to: (1) determine the effect of Canva-based video media on students’ learning outcomes in Christian Religious Education, and (2) compare the learning outcomes of students who learned using Canva-based video media with those who learned through conventional instructional methods. This study employed a quantitative approach with a quasi-experimental design. The research subjects consisted of 18 students from Class VIII A as the experimental group and 12 students from Class VIII B as the control group. Data were collected through pre-tests and post-tests using a 30-item multiple-choice test instrument covering cognitive domains C1–C4. Data analysis was conducted using the Wilcoxon Signed Rank Test for the first hypothesis and the Welch t-test for the second hypothesis. The results showed that: (1) there was a significant effect of using Canva-based video media on students’ learning outcomes in Christian Religious Education (Sig. = 0.000 < α = 0.05), with the experimental group achieving a mean post-test score of 76.00, exceeding the Minimum Mastery Criterion, and a mastery level of 72.22%; and (2) inferential statistical analysis indicated no significant difference between the gain scores of the experimental group (-17.61) and the control group (-19.42) (Sig. = 0.767 > α = 0.05). Nevertheless, descriptively, the experimental group demonstrated superior performance in terms of mean post-test scores, mastery percentage, and consistency of learning outcomes